Biomonitoring of Air Quality Using Lichen as Bioindicator in The Greater Bandung Area, West Java - Saragih, Dora Erawati; Irwanto, Rina Ratnasih; Taufikurahman, Taufik (School of Life Sciences and Technology, Institut Teknologi Bandung, 2024)
Air quality assessment in an area can be determined by conducting biomonitoring using bioindicator organisms, including lichen. Lichen is a symbiotic organism that passively absorbs nutrients and chemical compounds from the air. This research was conducted in the Greater Bandung area, including Bandung City and West Bandung Regency, to observe the abundance of lichen species so that the purity of the atmosphere could be evaluated at each research location and determine the effect of environmental variables on lichen abundance.The survey area was divided into 40 units spread over two locations in Bandung, namely Djuanda street (JD), Kebon Kawung street (KK), and two locations in West Bandung Regency, namely Padalarang street (PD) and Curug Cimahi (CC). CC locations with low levels of pollution were used as comparison areas. Lichen samples from observation locations were identified, and the number of colonies, frequency of closure, and diversity (H’) were counted so that the Index of atmospheric purity (IAP) value at each observation location could be known. As many as 24 species from 14 lichen families with a total of 256 colonies were found in the four observation sites with the percentage of thallus crustose (62%), foliose (37%), and fruticose (1%). The highest lichen diversity was found in the CC area (2.62), followed by JD (1.99), PD (1.63), and the lowest in KK (0.90). The lowest IAP result was in KK (10.21), followed by PD (17.70) and JD (31.85). The location with the highest IAP was obtained at CC (46.65), indicating that the environmental conditions were still good, while other locations were polluted.